Dynamics of the Development of Halal Guarantees Indonesia in the Framework of Islamic Economics - Karmila, Yusri; Siradjuddin; Kessi, Andi Muhammad Fara; Supatminingsih, Tuti (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research is to describe the dynamics of the development of halal guarantees in Indonesia through a qualitative approach. The research method is a qualitative descriptive analysis, during which information from various sources, including legal regulations, scientific journals and official documents, is examined. The dynamics of the development of halal guarantees in Indonesia show progress, but challenges still need to be addressed. Effective regulations, industry readiness and public understanding are the most important keys to the success of a halal guarantee system. In the Islamic economic framework, the halal guarantee must be seen as an effort to achieve sustainable prosperity and social justice. The qualitative approach of this study provides a deeper understanding of the various aspects that affect the halal guarantee in Indonesia. The researcher's proposal is that the government should continue to improve the regulation related to halal guarantees, including specifying the roles and responsibilities of different institutions. For example, 1) Supporting SMEs, 2) Information and awareness campaigns 3) Cooperation and synergy.